Telling the bees [large type] - Hesketh, Peggy (Thorndike Press, 2013)
Octogenarian Albert Honig's most constant companions have always been his bees. Deeply acquainted with the workings of hives, Albert is less versed in the ways of people, especially his friend Claire, whose presence and absence in his life have never been reconciled. When Claire is killed during a burglary gone wrong, Albert is haunted by the loss and by the secrets and silence that hovered between them for so long. Piecing together their shared history, Albert will come to learn both painful truths and the redemptive power of laying the past to rest.